2020
DOI: 10.1186/s12913-020-05580-0
|View full text |Cite
|
Sign up to set email alerts
|

Engendering health systems in response to national rollout of dolutegravir-based regimens among women of childbearing potential: a qualitative study with stakeholders in South Africa and Uganda

Abstract: Background: In the era of rapid dolutegravir rollout, concerns about neural tube defects have complicated the health systems response among women of childbearing potential. This qualitative study, which was nested within the DolPHIN-2 clinical trial, examined the current and future health system opportunities and challenges associated with the transition to dolutegravir-based regimen as first line antiretroviral therapy among women of childbearing potential in South Africa and Uganda. Method: Semi-structured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…Notably, information needs vary from patient to patient. There is need for sufficient, reliable and adequate information about risks and benefits of switching to DTG among people already on ART [ 9 ]. Some patients were concerned about questions related to dosing, adverse events, and reproductive needs (Additional file 1 , Additional file 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Notably, information needs vary from patient to patient. There is need for sufficient, reliable and adequate information about risks and benefits of switching to DTG among people already on ART [ 9 ]. Some patients were concerned about questions related to dosing, adverse events, and reproductive needs (Additional file 1 , Additional file 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study builds on previous research in which researchers showed that DTG is superior to existing treatment regimens and has a more tolerable side-effect profile [ 3 ]. Drug switching was driven by the potential direct health benefits of DTG to patients over current first line EFV-based regimens [ 9 ], including increasing pre-treatment resistance to NNRTIs, fewer side effects, rapid viral suppression and low pill burden [ 22 ]. Pill burden (number of tablets taken daily or large tablet size) is associated with suboptimal adherence [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As LMICs roll-out dolutegravir-based regimens in their HIV treatment programmes, a key question is how communities perceive the risks and benefits of the transition. The potential risks of dolutegravir in pregnancy could profoundly influence community acceptability and attitudes towards its use in women of childbearing age [ 19 ]. Women may lack accessible information and services and may face difficulties in decision-making despite WHO guidelines emphasising individual choice.…”
Section: Introductionmentioning
confidence: 99%